Upaya Meningkatkan Hasil Belajar Tema 1 Sub Tema 1 Ciri-Ciri Mahluk Hidup Menggunakan Model Problem Based Learning Di Kelas III SD Negeri 104201 Kolam T.A 2022/2023 - Sitorus, Mawar (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
The problem in this research is that students' classical completeness in class III-B SD Negeri 104201 Kolam has not reached 85%. This is because the selection of the learning model that the teacher applies is not in accordance with the material in Tema 1 Sub Tema 1 Ciri-Ciri Mahluk Hidup. The purpose of this study was to improve student learning outcomes in Tema 1, Sub Tema Ciri-Ciri Mahluk Hidup. This type of research is class action research (Classroom Action Research), with the research subject being Class III-B Students of SD Negeri 104201 Kolam for the 2022/2023 academic year. A total of 22 students, with details of 9 male students and 13 female students. The object of this research is the learning outcomes of students. This research was carried out in two learning cycles. 4 (are four) stages in each cycle, namely planning, implementation, observation, and reflection. The results of data analysis from 22 students obtained classical completeness in the initial pretest before using theÂ Problem Based Learning (PBL) model, namely 27.27%. The acquisition of the first cycle significantly increased with 54.55% classical completeness and was followed up in the second cycle with 90.91% classical completeness. Based on this analysis it was concluded thatÂ Problem Based LearningÂ (PBL) can improve the learning outcomes of students in Teme 1 Sub Teme 1 Ciri-Ciri Mahluk Hidup in Class III Students of SD Negeri 104201 kolam for the 2022/2023 Academic Year.